I assume you want to find a and b so it divides evenly?
x^3 + 2(a-2b)x^2 - b(8a-3b)x + 6ab^2
= x^2 - 4bx + 3b^2 remainder 6ab(1-b)
so, to divide evenly, either a=0 or b=1
a=0: x^3 - 4bx^2 + 3b^2x + 0 = x(x^2-4bx+3b^2) for any b
b=1: x^3 + 2(a-2)x^2 - (8a+3)x + 6a
= (x+2a)(x^2 - 4x - 3) for any a
Answer this Question
algebra - factor 6ab - 8b YOu can factor a 2b out of it.
algebra 1 - factor 6ab-8b: Common factor: 2b 2b (3a-4)
Algebra - Multiply 5a^3+4a^2 8b^6-6ab^6 _________ * __________ 6ab-8b 5a^2+4a
algebra - factor the expression a^2-6ab+9b^2 into a product of binomials
Math - Factor completely. 36a^3b^2+66a^2b^3-210ab^4 Is this correct? 6ab^2(6a^2+...
Maths (factor theorem) - 9x^2 6xy 4y^2 is a factor of 27x^3 - 8y^3, find the ...
algebra - simplify 2a^2 + 6ab^2-12a^2b^3 divided by 24ab -2a^2/-24ab + 6ab^2/...
maths - Use a factor tree to write 1575 as a product of prime factors. You ...
Algebra - (3a^2+6ab-a-2b)/(9a^2-6a+1)
Algebra - (9a^3b^4-12a^2b^5+6ab^7)/(6a^2b^3)